HOW TO BECOME A PSYCHOLOGIST: ERIC BERN'S TRANSACTIONAL ANALYSIS (Universal International Scientific Journal, 2026)
In modern society, the importance of the profession of a psychologist in ensuring human health and well-being is increasing. Especially at a time when stress, competition, social inequality and spiritual searches in a market economy put pressure on the human psyche, the need for qualified psychologists is becoming an urgent issue. A psychologist should not be limited only to diagnostics and counseling, but also be a specialist who can analyze social and cultural processes, and also work in areas such as personal development, family problems, conflicts in labor teams, and adaptation processes of youth and children. However, the use of psychological services in society still remains complex. Several factors contribute to this situation. First of all, the mental health culture of the population is not sufficiently formed. Secondly, some individuals providing psychological services have low qualifications or their activities do not have a scientific basis at all. This exacerbates the problems of distinguishing real and fake specialists. In addition, regulatory mechanisms related to psychological services are not sufficiently formed in the legislation. As a result, situations are arising that undermine the reputation of the psychology profession.
Keywords: A real psychologist is the first